A study of resilience and professional hardiness among participants of specialization courses in the field of mental health care during wartime - Nikolenko, Алла; Ogorenko, Вікторія; Shusterman, Тамара; Kokashynskyi, Віктор (Psychosomatic Medicine and General Practice, 2025)
Introduction. In times of war, doctors and professionals with higher non-medical education in psychological assistance in healthcare face unprecedented challenges that affect their professional activities, psycho-emotional state, and resilience. Resilience and professional endurance determine the ability to adapt, maintain performance, and prevent burnout, and studying them is crucial for supporting specialists and strengthening the medical community. Constant stress, high responsibility, and moral-ethical dilemmas create a significant burden, especially for those undergoing training in specialization cycles, particularly during martial law. The aim of this study is to investigate the level of resilience and professional endurance of participants in specialization cycles in mental health care during the war, as well as to assess their personal anxiety to prevent professional burnout. The purpose of this study is to investigate the level of resilience and professional endurance of participants in specialization cycles in mental health care during the war, as well as to assess their personal anxiety in order to prevent professional burnout. Methods. A psychodiagnostic study of resilience and professional endurance was conducted on 30 participants of specialization cycles in mental health care during the war using psychometric scales (Connor-Davidson Resilience Scale-10 (CD-RISC-10); State-Trait Anxiety Inventory (STAI); Professional Endurance Questionnaire (Kokun O.M., 2021). Results. According to the CD-RISC-10 scale, the stress resilience level in the sample was moderate, with men showing a low level and women a moderate level. The level of personal anxiety in the sample overall and by gender was moderate. The level of professional endurance was higher than average overall, higher among women, and high among men. No statistically significant difference was found between the scores on all scales for men and women. More than half of the participants (57%) demonstrated a moderate level of personal anxiety. The most common levels of stress resilience among the study participants were average and above average. Half of the participants showed a high level of professional endurance, but nearly one in four had a low or below-average level of professional endurance. Among the components of professional endurance, the professional control component was predominant in the general sample and among both genders. In the overall sample and among women, the motivational component of professional endurance prevailed, while among men, the social component was more prominent. Discussion. The participants in our study demonstrated a higher-than-average level of stress resilience, which can be attributed to the impact of prolonged war events in Ukraine, combined with the previous crisis experience caused by the pandemic. Our findings regarding moderate levels of anxiety align with both Ukrainian and international research. Furthermore, a comparison of professional endurance between our study and the All-Ukrainian survey (2022) showed that our participants had an above-average level. The absence of a correlation with years of experience suggests effective adaptation and the development of professional confidence, which reduces the risk of burnout, although individual cases of increased vulnerability to stress, particularly during the war, are still possible. Conclusion. Overall, the level of stress resilience among participants in specialization cycles in mental health care during the war was moderate, with men showing a low level and women a moderate level. Personal anxiety in the studied sample was predominantly at a moderate level, including by gender. The overall level of professional endurance was higher than average. Among the components of professional endurance, the motivational component prevailed in the general sample and among women, while the social component was more dominant among men. The highest level among the components was professional control. The obtained results can be used to develop support programs for healthcare workers and mental health professionals aimed at enhancing resilience and preventing professional burnout during martial law and post-war recovery.